Community structure of Mangroves in Laua-an, Antique. - Selis, Mary Grace (2006.)
The study generally aims to assess the community structure of mangroves in Laua-an, Antique.
There is a continous decline of mangroves in the Philippines. However, they remain poorly undocumented. Thus need of the present study to provide baseline information needed for a proper management of the remaining mangroves. This study generally aims to assess the community structure of mangroves in Laua-an, Antique. Specifically, it aims to: 1) measure physico-chemical parameters that influence local species distribution and growth; 2) determine the Species composition. Nypa fruiticans is the only mangrove species in this municipality and most of them are planted and harvested by the community. An attempt was made to correlate the number of dead (harvested), and living (immature) to determine sustainability of production. Results showed that the number of harvested was greater than the number of young or immature of Nypa fruiticans, Station 3 having the tallest height, biggest clump size, highest number of harvested and young stems was the oldest community. Station 2 had the shortest height, smallest clump size and the lowest number of harvested stems which indicate that it is still in its first year of harvesting. Height, clump size and the number of young and harvested stems can correlate with the age of nipa growing in the community. All the stations can be considered in a sustainable level. Water pH ranged from 7.15-7.47; water temperature 29.22-31.25; soil temperature 29.5-30.5;soil pH 6.21-6.85 and water salinity 1.73-8.06. Nipa palms grow only on tidal lands near the sea and thrived on swampy, saline soils along seashore and riverbanks which has quite acidic soil pH and a very wide range of water salinity that is basically influenced by tides., Education of the value of nipa community is essential to maintain sustainable level and reap alot of advantages without destruction.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mangroves -- Laua-an, Antique